2017
DOI: 10.1044/2017_jslhr-s-16-0113
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions Impact the Relation Between Respiratory Sinus Arrhythmia and Frequency of Stuttering in Young Children Who Do and Do Not Stutter

Abstract: Findings suggest that decreased RSA during video viewing and speaking is associated with increased stuttering and young CWS differ from CWNS in terms of how their executive functions moderate the relation between RSA change and stuttered disfluencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 101 publications
2
31
0
1
Order By: Relevance
“…These reports are consistent with findings of slower response times compared to CWNS, and a negative correlation between accuracy and speed in CWS using direct measures of attention (e.g., Dimensional Card Change Sort, Posner Test of Covert Attention Shift) which require target selection and shifting attention toward different cues [ 9 , 103 , 104 ]. Weaker attention control is also correlated with higher frequency of stuttering in CWS [ 105 , 106 ]. Similarly, in adults who stutter divided attention, i.e., managing concurrent tasks (e.g., speech and finger tapping), results in higher rates of stuttering [ 107 however, see 108 ].…”
Section: Introductionmentioning
confidence: 99%
“…These reports are consistent with findings of slower response times compared to CWNS, and a negative correlation between accuracy and speed in CWS using direct measures of attention (e.g., Dimensional Card Change Sort, Posner Test of Covert Attention Shift) which require target selection and shifting attention toward different cues [ 9 , 103 , 104 ]. Weaker attention control is also correlated with higher frequency of stuttering in CWS [ 105 , 106 ]. Similarly, in adults who stutter divided attention, i.e., managing concurrent tasks (e.g., speech and finger tapping), results in higher rates of stuttering [ 107 however, see 108 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent theoretical account of childhood stuttering suggests that emotional processes may also be associated with the onset and the development of childhood stuttering (Conture & Walden, 2012). Furthermore, findings from numerous empirical studies conducted over the past decade lend support to the possible association between emotional processes and childhood stuttering (e.g., Anderson, Pellowski, Conture, & Kelly, 2003; Arnold, Conture, Key, & Walden, 2011; Choi, Conture, Walden, Jones, & Kim, 2016; Choi, Conture, Walden, Lambert, & Tumanova, 2013; Clark, Conture, Walden, & Lambert, 2015; Eggers, De Nil, & Van den Bergh, 2010, 2012, 2013; Felsenfeld, van Beijsterveldt, & Boomsma, 2010; Johnson, Walden, Conture, & Karrass, 2010; Jones, Buhr, et al, 2014; Jones, Conture, & Walden, 2014; Jones, Walden, Conture, Erdemir, Lambert & Porges, 2017; Karrass et al, 2006; Ntourou, Conture, & Walden, 2013; Schwenk, Conture, & Walden, 2007; Walden et al, 2012; Zengin-Bolatkale, Conture, & Walden, 2015).…”
Section: Introductionmentioning
confidence: 83%
“…Participants were recruited through the following methods in the metropolitan Nashville, Tennessee area: (a) a free, regionally-distributed parent-oriented magazine, (b) local health care provider referrals, or (c) self/professional referral to the Vanderbilt Developmental Stuttering Laboratory. Participants were part of an ongoing series of investigations of linguistic and emotional contributors to developmental stuttering conducted by the Vanderbilt University Developmental Stuttering Project (Arnold, Conture, Key, & Walden, 2011; Choi, Conture, Walden, Lambert, & Tumanova, 2013; Choi et al, 2016; Clark, Conture, Frankel & Walden, 2012; Clark, Conture, Walden, & Lambert, 2013, 2015; Johnson, Walden, Conture, & Karrass, 2010; Jones et al, 2014; Jones, Conture, & Walden, 2014; Jones et al, in press; Ntourou, Conture, & Walden, 2013; Tumanova, Conture, Lambert & Walden, 2014; Zengin-Bolatkale, Conture, & Walden, 2015). The study’s protocol was approved by the Institutional Review Board of Vanderbilt University.…”
Section: Methodsmentioning
confidence: 99%
“…Overall findings across several empirical studies/reviews suggest that, despite equivocal findings, childhood stuttering might be associated with delayed speech-language abilities (e.g., Pellowski, Anderson & Conture, 2000; Bloodstein & Ratner, 2008; Murray & Reed, 1977; Ntourou et al, 2011; Ratner & Silverman, 2000) and poorer attentional processes (e.g., Eggers, Luc, Van den Bergh, 2010, 2012; Felsenfeld, van Beijsterveldt, & Boomsma, 2010; Karrass et al 2006; Jones et al, in press). For example, Arndt and Healey’s (2001) survey results from 241 speech-language pathologists revealed that 14.1% of children who stutter (CWS) have phonological disorders (compared to 2–25% of children who do not stutter [CWNS], Law, Boyle, Harris, Harkness, & Nye, 2000), 15.4% of CWS have language disorders (compared to 2.63% to 16% of CWNS, Law et al, 2000) and 14.3% of CWS have both phonological and language disorders.…”
Section: Nature Of Vulnerability To Stutteringmentioning
confidence: 95%